The investigation of students' engagement in online class during pandemic Covid-19 - Tommy Hastomo; Linda Septiyana (Jurnal Penelitian Ilmu Pendidikan, 2022)
Students' engagement is the high level of cognitive, emotional, and behavioral engagement in the teaching-learning activity. This article research investigated the effects of collaborative classroom activities on student engagement in the virtual classroom. This research is mix-method research that consists of qualitative and quantitative research. The independent variable is collaborative classroom activities, and the dependent variable is students' engagement. The subjects of this research are students from two different universities in Lampung. The researchers use questionnaires to collect the quantitative data and employ observation and take notes to collect the qualitative data. The researchers use TPT Cognitive Engagement Model and Quadrant Analysis for analyzing the data of research. The findings show the same level of students engagement in both quadrants three and four in both classes taught by both researchers. Analysis of students' engagement can be analyzed accurately if the use of peer-coaching techniques is carried out. In addition, the material on subject writing can be studied effectively, and students can also get motivated through collaborative learning based on research survey data.Investigasi keterlibatan siswa di kelas online selama pandemi Covid-19Keterlibatan siswa merupakan tingginya tingkat keterlibatan kognitif, emosional, dan perilaku siswa dalam kegiatan belajar-mengajar. Penelitian artikel ini bertujuan untuk menyelidiki efek dari kegiatan kelas kolaboratif pada keterlibatan siswa di kelas virtual. Penelitian ini merupakan penelitian metode campuran yang terdiri dari penelitian kualitatif dan kuantitatif. Variabel bebasnya adalah aktivitas kelas kolaboratif, dan variabel terikatnya adalah keterlibatan siswa. Subyek penelitian ini adalah mahasiswa di dua perguruan tinggi yang berbeda di Lampung. Peneliti menggunakan kuesioner untuk mengumpulkan data kuantitatif dan menggunakan observasi dan mencatat untuk mengumpulkan data kualitatif. Model TPT Cognitive Engagement dan Analisis Kuadran digunakan oleh peneliti untuk menganalisis data penelitian. Temuan menunjukkan tingkat yang sama dari keterlibatan siswa di kedua kuadran tiga dan empat di kedua kelas yang diajarkan oleh kedua peneliti. Analisis engagement siswa dapat dianalisis secara akurat jika dilakukan penggunaan teknik peer-coaching. Selain itu, materi tentang penulisan mata pelajaran dapat dipelajari secara efektif, dan siswa juga dapat termotivasi melalui pembelajaran kolaboratif berdasarkan data survei penelitian.